Impact of the Hepatopulmonary Syndrome MELD Exception Policy on Outcomes of Patients After Liver Transplantation: An Analysis of the UNOS Database - Goldberg, David S. (2014)
BACKGROUND & AIMS: Patients with hepatopulmonary syndrome (HPS) are prioritized for liver transplantation (given exception points) due to their high pre- and post-transplantation mortality. However, few studies have evaluated the outcomes of these patients. METHODS: We performed a retrospective cohort study using data submitted to the United Network for Organ Sharing in a study of the effects of room-air oxygenation on pre- and post-transplantation outcomes of patients with HPS. We identified thresholds associated with post-transplantation survival using cubic spline analysis and compared overall survival times of patients with and without HPS. RESULTS: From 2002 through 2012, nine hundred and seventy-three patients on the liver transplant waitlist received HPS exception points. There was no association between oxygenation and waitlist mortality among patients with HPS exception points. Transplant recipients with more severe hypoxemia had increased risk of death after liver transplantation. Rates of 3-year unadjusted post-transplantation survival were 84% for patients with PaO(2) of 44.1–54.0 mm Hg vs 68% for those with PaO(2) ≤ 44.0 mm Hg. In multivariable Cox models, transplant recipients with an initial room-air PaO(2) ≤ 44.0 mm Hg had significant increases in post-transplantation mortality (hazard ratio = 1.58; 95% confidence interval [CI]: 1.15–2.18) compared with those with a PaO(2) of 44.1–54.0 mm Hg. Overall mortality was significantly lower among waitlist candidates with HPS exception points than those without (hazard ratio = 0.82; 95% CI: 0.70–0.96), possibly because patients with HPS have a reduced risk of pre-transplantation mortality and similar rate of post-transplantation survival. CONCLUSIONS: Although there was no association between pre-transplantation oxygenation and waitlist survival in patients with HPS Model for End-Stage Liver Disease exception points, a pre-transplantation room-air PaO(2) ≤ 44.0 mm Hg was associated with increased post-transplantation mortality. HPS Model for End-Stage Liver Disease exception patients had lower overall mortality compared with others awaiting liver transplantation, suggesting that the appropriateness of the HPS exception policy should be reassessed.